Antibacterial and antibiofilm activity of Albizia lebbeck leaves extracts in Pseudomonas aeruginosa isolated from urinary tract infection - Abdulaal, Inas Humam; AL-Azawi, Ahmed H.; Yahya, Diana Ghanem (ScienceRise: Pharmaceutical Science, 2025)
Microbial infections have become one of the most pressing public health issues worldwide as a result of the emergence of resistance to current antibiotics. This has prompted scientists to examine the antibacterial characteristics of medicinal plants. The aim of the study: Extract secondary metabolites from Albizia lebbeck and analyze how they affect Pseudomonas aeruginosa. Materials and methods: From the labs of the University of Baghdad's Genetic Eng. and Biotech. Institute, 10 isolates of P. aeruginosa were obtained. The identification was confirmed by cultivating the isolates on cetrimide agar and using the VITEK2 technology. Results: The chemical analysis of the methanolic and aqueous extracts revealed the presence of secondary metabolite molecules such as alkaloids, flavonoids, glycosides, phenols, saponins, and tannins. The total phenols content of the methanolic and aqueous extracts was 71.11 mg/g and 45.15 mg/g, respectively. Furthermore, the results indicated that at a concentration of 50 mg/ml, the methanolic extract outperformed the aqueous extract in free radical scavenging by 78. 65% to 91. 20%. Using the disk diffusion method, the methanolic extract also demonstrated higher antibacterial activity than the aqueous extract of Albizia lebbeck leaves, and its potency increased with increasing concentration. The methanolic extract's lowest inhibitory concentration against P. aeruginosa isolates was determined to be 16 mg/ml, whereas the aqueous extract's was 32 mg/ml. According to the biofilm formation experiment, the methanol extract inhibits the formation of biofilms at a concentration of 200 mg/ml, whereas the aqueous extract does so at a concentration of 400 mg/ml. Conclusion: This work demonstrated that the secondary metabolites extracted from Albizia lebbeck leaves have a considerable antibacterial and antibiofilm action on P. aeruginosa, even though the bacterial isolates create a strong biofilm. This research has shown that Albizia lebbeck leaves can be used in traditional therapy for bacterial infections and diseases caused by oxidative stress since they contain therapeutic phytochemicals with strong antibacterial and antioxidant effects